Efeito de níveis de irrigação em substratos para a produção de mudas de ipê-roxo - Sabonaro, Débora Zumkeller [UNESP]; Galbiatti, João Antonio [UNESP] (My University, 2007)
The aim of this work was to evaluate the ipê-roxo (Tabebuia impetiginosa (Mart.) Standl). seedlings behavior in different substrates and irrigation levels and also study the use of urban waste compost in the substrates. The experiment was conducted in the agricultural engineering department at the Faculdade de Ciências Agrárias e Veterinárias - UNESP, Campus de Jaboticabal, SP. The experimental design used was the completely randomized with 30 treats and 2 replicates, in a 15× 2 factorial arrangement [15 substrates and 2 irrigation levels (100% and 150% of evapotranspiration)]. The substrates were composed by different material combinations: urban waste, Plantmax, tanned cattle manure, vermiculite and soil. For the study of the seedlings development, the following characteristics were evaluated: the seedlings height (H) and stem diameter (D). Evaluations (H and D) were made on 90, 105, 120, 135 and 150 days after sowing. The statistical analysis showed significant differences between the irrigation levels. According to the results, we can conclude that urban waste compost did not increase Blake development. For tested irrigation levels, the statistical analysis showed significant differences with better results for the 150% ET irrigation level compared to 100% ET.
Effect of irrigation levels in substrates for ipê-roxo seedlings production
Keywords: Irrigation; Seedlings; Substrate; Urban solid waste; Irrigation levels; Tanned cattle manure; Agricultural engineering; Refuse composting; Seed; Waste management